Transformation of Traditional Food with Duck Basic for Culinary Business Continuity in Ubud Tourist Village, Gianyar, Bali, Indonesia - Sutaguna, I Nyoman Tri; Sirna, I Ketut; Utama, I Gusti Bagus Rai (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Ubud Village, which is one of the attractions for tourists to visit the island of Bali, has a very beautiful and beautiful view. Tourists who visit Ubud not only enjoy the physical views of natural and man-made resources but they also want to learn about the original Balinese culture that breathes Hinduism. One thing that tourists can learn from Balinese culture is enjoying traditional Balinese food (culinary tours). This study aims to identify traditional Balinese food made from duck meat in terms of (1) The transformation product of traditional Balinese food made from duck and (2) Food contained in traditional Balinese food. The informants were determined by selecting restaurants and restaurants that sell traditional Balinese food which had been transformed and determined based on the purposive sampling method. Determination of information from tourists used in-depth interviews with resource persons who are competent in their fields. Data collection techniques are using observation, interviews, and documentation. The presentation of the research results is described quantitatively and qualitatively. Transformation processes such as texture, shape, taste, color, the aroma of the processing process, and attractive presentation methods, taking into account sanitary, hygienic, and food safety standards. Furthermore, the meaning of the transformation of traditional Balinese food made from a duck that has been developed is in the form of economic meaning, social meaning, ethical meaning, and aesthetic meaning. This will be able to provide added value to tourists and the community in Ubud Tourism Village.